Gear, worm gear and robot

By using a combination of specific polyarylene sulfide resin, cellulose nanofibers and silane coupling agent, the durability and dimensional accuracy of resin-made gears under high temperature and high humidity are solved, and low dimensional change rate and high durability are achieved. Improved silentness and heat resistance.

CN119173705APending Publication Date: 2024-12-20DIC CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380038281.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-01
Filing Date
2023-03-27
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing resin-made gears are difficult to maintain durability and dimensional accuracy under high temperature or high humidity, and the compatibility between the reinforcement materials and thermoplastic resins in the prior art is insufficient, resulting in a decrease in mechanical strength and durability.

Method used

The composition containing specific polyarylene sulfide resin (PAS resin) as the main component is used, combined with cellulose nanofibers and silane coupling agent, and the melt viscosity is controlled within the range of 50Pa·s to 4000Pa·s, to improve the durability of the gear and Mold transferability.

Benefits of technology

The dimensional change rate caused by low heat and water absorption is achieved, the gear durability and dimensional accuracy at high temperature and high humidity are improved, the eccentricity or tooth thickness deviation is reduced, and the quietness and heat resistance are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119173705A_ABST
    Figure CN119173705A_ABST
Patent Text Reader

Abstract

The purpose of the present disclosure is to provide a gear, a worm gear, and a robot which have a low rate of dimensional change due to thermal expansion and water absorption even when a resin gear is used, and which have excellent durability and dimensional accuracy at high temperatures and high humidity. The present disclosure is a gear having, as a constituent component, a polyarylene sulfide resin having a melt viscosity (V6) of 50 Pa.s to 4000 Pa.s, the gear having a first tooth portion formed on the outer periphery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a gear, a worm gear and a robot. Background Art

[0002] In recent years, from the perspective of lightweight, maintenance-saving (grease-free) or quieting of robots, there is a demand for resinization of existing metal gears, and POM or PA is used as the material of the sliding part of the gear or bearing. For example, Patent Document 1 discloses a resin gear containing a thermoplastic resin and cellulose nanofibers (hereinafter also referred to as CNF) with an average fiber diameter of less than 1000nm. In addition, Patent Document 2 discloses a gear having a metal core tube and an annular resin portion integrally provided on the outer periphery of the core tube and having a plurality of gear teeth formed on the outer periphery.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2020-108959

[0006] Patent Document 2: Japanese Patent Application Publication No. 2016-064714 Summary of the invention

[0007] Problems to be solved by the invention

[0008] As with existing metal gears, resin gears are also required to have material properties such as thermal stability, water absorption, mechanical strength and dimensional stability. However, in the technologies of Patent Documents 1 and 2, it is impossible to obtain resin gears that meet the durability and dimensional accuracy under high temperature or high humidity. For example, in the technology of Patent Document 1, CNF itself is difficult to disperse in the thermoplastic resin due to its own coagulation, resulting in a problem of reduced mechanical strength or durability. In addition, in the technology of Patent Document 2, a resin material containing a reinforcing material including soft fibers and a thermoplastic resin is used to form the gear teeth on the outer peripheral surface, but the compatibility of the reinforcing material with the thermoplastic resin is not studied, so the adhesion of the reinforcing material with the thermoplastic resin is insufficient, and as a result, it is impossible to obtain a gear that is sufficiently practical and has durability and dimensional accuracy under high temperature or high humidity.

[0009] Therefore, an object of the present disclosure is to provide a gear, a worm gear, and a robot that have a low dimensional change rate due to heat and water absorption even if the gear is made of resin and have excellent durability and dimensional accuracy under high temperature and high humidity.

[0010] Methods for solving problems

[0011] The present inventors have conducted intensive research on methods for solving the above-mentioned problems. As a result, they have found that the above-mentioned problems can be solved by using a PAS resin composition containing a specific polyarylene sulfide resin (hereinafter referred to as PAS resin) as a main component, thereby completing the present invention. That is, the present disclosure is as follows.

[0012] [1] The present disclosure is a gear having a first tooth portion formed on an outer circumference and containing a polyarylene sulfide resin having a melt viscosity (V6) of 50 Pa·s to 4000 Pa·s as a constituent component.

[0013] [2] The gear according to [1] above, wherein the dimensional change rate (%) due to a temperature change from 0°C to 80°C represented by the following formula (I) is 0.7% or less.

[0014] [Number 1]

[0015]

[0016] (In the formula (I), L 80 Indicates the addendum diameter of the gear at 80°C, L 0 Indicates the tip circle diameter of the gear at 0°C)

[0017] [3] The gear according to [1] or [2], further comprising cellulose nanofibers as the constituent component, wherein the content of the cellulose nanofibers is less than 0.5% by mass relative to the total amount of the polyarylene sulfide resin and the cellulose nanofibers.

[0018] [4] The gear according to any one of [1] to [3] above, further comprising a silane coupling agent as the constituent component.

[0019] [5] A worm gear comprising: the gear as described in any one of [1] to [4] above as a worm wheel, and a worm having a second tooth portion meshing with a first tooth portion of the gear,

[0020] The worm includes a polyarylene sulfide resin having a melt viscosity (V6) of 50 Pa·s to 4000 Pa·s as a constituent component.

[0021] [6] A gear system for a robot, comprising the worm gear described in [5] above.

[0022] [7] A robot comprising the robot gear system described in [6] above.

[0023] Effects of the Invention

[0024] According to the present disclosure, there are provided a gear, a worm gear, and a robot having a low dimensional change rate due to heat and water absorption and having excellent durability and dimensional accuracy under high temperature and high humidity.

[0025] According to the present disclosure, a worm wheel or a worm gear having good dimensional accuracy and excellent durability and positioning is provided, a worm wheel, a worm gear, or a robot. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a schematic diagram showing an example of a worm gear as an example of a gear according to an embodiment of the present disclosure.

[0027] Figure 2 This is a schematic diagram showing an example of a worm as an example of a gear according to an embodiment of the present disclosure.

[0028] Figure 3 It is a schematic diagram showing an example of the structure of a worm gear according to one embodiment of the present disclosure.

[0029] Figure 4 Is has Figure 3 Schematic diagram of the worm gear robot arm mechanism. DETAILED DESCRIPTION

[0030] Hereinafter, a mode for carrying out the present invention (hereinafter referred to as “the present embodiment”) will be described in detail, but the present invention is not limited to the following description and can be carried out with various modifications within the scope of the gist thereof.

[0031] The gear of the present embodiment has a first tooth portion formed on the outer circumference and includes a PAS resin having a melt viscosity (V6) of 50 Pa·s to 4000 Pa·s as a constituent component.

[0032] The gear of the present embodiment contains a PAS resin having predetermined characteristics, and thus has a low dimensional change rate due to heat and water absorption, and has excellent durability and dimensional accuracy under high temperature and high humidity.

[0033] By using a PAS resin with a melt viscosity (V6) of 50 Pa·s or more, the strength of the PAS resin constituting the gear becomes higher, thereby improving the durability of the entire gear. On the other hand, by using a PAS resin with a melt viscosity (V6) of 4000 Pa·s or less, the PAS resin can be filled to the tooth top during injection molding, thereby improving the mold transferability of the gear and making it possible to produce a gear with a good appearance.

[0034] The so-called "PAS resin as a constituent component" mentioned here means that the material constituting the gear contains PAS resin. Therefore, as long as the material constituting the gear contains PAS resin, the material constituting the gear may be PAS resin, or may be a PAS resin composition containing PAS resin as a main component.

[0035] In addition, the "PAS resin composition containing a PAS resin as a main component" in this specification means that the PAS resin is contained in an amount of 50% by mass or more relative to the total amount (100% by mass) of the PAS resin composition.

[0036] The gear of this embodiment contains PAS resin, and has a flat plate-shaped main body, and a first tooth portion provided on the outer periphery (i.e., radially outward) of the main body. Therefore, the gear of this embodiment has a low dimensional change rate due to heat and water absorption, and has excellent durability and dimensional accuracy under high temperature and high humidity. Therefore, it is considered that eccentricity or tooth thickness deviation is not likely to occur, and shaking can be reduced during use.

[0037] Preferred forms of the gear of the present embodiment may be a worm, a worm wheel, or a worm gear including a worm and a worm wheel having a tooth surface meshing with the worm.

[0038] The so-called general gears are in rolling contact, while the worm gears are in sliding contact, so they are excellent in quietness, but there is a problem of heat generation. However, since the gears of this embodiment contain PAS resin, they are excellent in quietness and heat resistance even without grease, and they exhibit excellent performance in both rolling contact gears and worm gears. In particular, since the gears of this embodiment have a low dimensional change rate caused by heat and water absorption, and have excellent durability and dimensional accuracy under high temperature and high humidity, it can be considered that when the gears of this embodiment are used as worms, worm wheels or worm gears, they are effective by reducing deviations in eccentricity or tooth thickness, and shaking during use.

[0039] Hereinafter, after describing the PAS resin constituting the gear of the present embodiment, a method for producing the PAS resin, and a PAS resin composition, a worm, a worm wheel, a worm-type gear, and a robot which are preferred gears of the present embodiment will be described in sequence using the drawings.

[0040] (PAS resin)

[0041] The PAS resin of the present embodiment is a resin having a melt viscosity (V6) of 50 Pa·s to 4000 Pa·s and having a structure in which an aromatic ring and a sulfur atom are bonded as a repeating unit. That is, the chemical structure of the PAS resin of the present embodiment has a resin structure in which a structure in which an aromatic ring and a sulfur atom are bonded as a repeating unit. Specifically, the PAS resin of the embodiment is preferably a resin in which a structural part represented by the following general formula (I) and a trifunctional structural part represented by the following general formula (2) are further contained as repeating units.

[0042] [Chemistry 1]

[0043]

[0044] (In the general formula (I), R 1 and R 2 Each independently represents a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, a nitro group, an amino group, a phenyl group, a methoxy group or an ethoxy group.)

[0045] [Chemistry 2]

[0046]

[0047] The trifunctional structural part represented by the general formula (2) is preferably in the range of 0.001 mol% to 3 mol%, and particularly preferably in the range of 0.01 mol% to 1 mol%, based on the total molar number of the trifunctional structural part and other structural parts.

[0048] Here, regarding the structural part represented by the general formula (I), from the viewpoint of the mechanical strength of the PAS resin, it is particularly preferred that R 1 and R 2 In this case, it is a hydrogen atom, and examples thereof include a structural part bonded at the para position represented by the following general formula (3) and a structural part bonded at the meta position represented by the following general formula (4).

[0049] [Chemistry 3]

[0050]

[0051] Among them, regarding the structural part represented by the general formula (I), it is particularly preferred that the sulfur atom in the repeating unit is bonded to the aromatic ring at the para position as represented by the general formula (3) from the viewpoint of heat resistance and crystallinity of the PAS resin.

[0052] In addition, the PAS resin may contain not only the structural parts represented by the general formula (I) and the general formula (2), but also the structural parts represented by the following general formulas (5) to (8) in an amount of 30 mol % or less of the total of the structural parts represented by the general formula (I) and the general formula (2).

[0053] [Chemistry 4]

[0054]

[0055] In particular, in the present embodiment, from the perspective of heat resistance and mechanical strength of the PAS resin, the structural parts represented by the general formulae (5) to (8) are preferably 10 mol% or less. When the PAS resin contains the structural parts represented by the general formulae (5) to (8), the combination thereof may be any of a random copolymer and a block copolymer.

[0056] The PAS resin of the present embodiment may also have a naphthyl sulfide bond or the like in its molecular structure, and the amount thereof is preferably 3 mol% or less, particularly preferably 1 mol% or less, based on the total molar number of other structural parts.

[0057] The melt viscosity (V6) of the PAS resin of the present embodiment is in the range of 50 Pa·s or more and 4000 Pa·s or less. The upper limit of the melt viscosity (V6) of the PAS resin of the present embodiment is preferably 2000 Pa·s or less, more preferably 700 Pa·s or less, and further preferably 300 Pa·s or less. In addition, the lower limit of the melt viscosity (V6) of the PAS resin of the present embodiment is preferably 70 Pa·s or more, more preferably 80 Pa·s or more, and further preferably 90 Pa·s or more. The upper and lower limits may be arbitrarily combined.

[0058] By using a PAS resin having a melt viscosity (V6) of 50 Pa·s or more and 4000 Pa·s or less, the overall durability of the gear can be improved, and a gear with good appearance can be produced. In addition, when the appearance of the molded gear is important, the melt viscosity (V6) of the PAS resin is preferably 50 Pa·s or more and 300 Pa·s or less. On the other hand, when the durability of the gear is important, the melt viscosity (V6) of the PAS resin is preferably 90 Pa·s or more and 4000 Pa·s or less.

[0059] The melt viscosity (V6) in this specification is measured by using a flow tester CFT-500D manufactured by Shimadzu Corporation on PAS resin at 300°C and a load of 1.96×10 6 Pa, L / D = 10 (mm) / 1 (mm) after holding for 6 minutes and measuring the melt viscosity.

[0060] The PAS resin of the present embodiment preferably has a carboxyl group in its molecule. The carboxyl group is reactive with a coupling agent, so when a coupling agent is further added as a constituent component, the gear durability can be improved by using the coupling agent in combination.

[0061] The content of carboxyl groups in the molecular structure of the PAS resin of the present embodiment is preferably 10 μmol or more and 200 μmol or less, more preferably 20 μmol or more and 100 μmol or less, and further preferably 20 μmol or more and 50 μmol or less, relative to 1 g of the PAS resin.

[0062] In the present specification, the amount of carboxyl groups contained in the PAS resin is measured using an FT-IR apparatus after preparing a pre-treated sample as described in the first example.

[0063] The non-Newtonian index of the PAS resin of the present embodiment is not particularly limited, and is preferably in the range of 0.90 to 2.00. In the case of using a linear PAS resin, the non-Newtonian index is preferably in the range of 0.90 or more, more preferably in the range of 0.95 or more, preferably in the range of 1.50 or less, and more preferably in the range of 1.20 or less. This kind of PAS resin has excellent mechanical properties, fluidity, and wear resistance. However, in the present disclosure, the non-Newtonian index (N value) is a value calculated using the following formula (II) by measuring the shear rate (SR) and shear stress (SS) using a capillary rheometer (capilograph) at a melting point of +20°C, a ratio of pore length (L) to pore diameter (D), and a ratio of L / D=40. The closer the non-Newtonian index (N value) is to 1, the closer it is to a linear structure, and the higher the non-Newtonian index (N value), the more advanced the branching structure.

[0064] [Number 2]

[0065] SR=K·SS N

[0066] [Wherein, in the above formula (II), SR represents the shear rate (seconds) -1 ), SS represents shear stress (dyne / cm 2 ), and K represents a constant. ]

[0067] The peak molecular weight (hereinafter also referred to as M) of the PAS resin of the present embodiment is top ) is preferably in the range of 30,000 to 80,000, more preferably in the range of 32,000 to 72,000, and still more preferably in the range of 35,000 to 46,000. topThe lower limit of M is preferably 30,000 or more, more preferably 32,000 or more, and further preferably 35,000 or more. top The upper limit of is preferably 80000 or less, more preferably 72000 or less, and further preferably 46000 or less. The upper limit and the lower limit may be arbitrarily combined.

[0068] The M of the PAS resin of this embodiment w / M top It is preferably in the range of 0.80 to 1.70, and more preferably in the range of 0.90 to 1.30. w / M top When the M is within such a range, the processability of the PAS resin can be improved and a good cavity balance can be provided. w represents the weight average molecular weight determined by gel permeation chromatography, M top It represents the average molecular weight (peak molecular weight) at the point where the detection intensity of the chromatogram obtained by the above measurement becomes maximum. w / M top Indicates the distribution of the molecular weight of the measurement object. Generally, when the value is close to 1, it means that the molecular weight distribution is narrow, and as the value increases, it means that the molecular weight distribution is broad.

[0069] It should be noted that the peak molecular weight determination method in this specification is based on the value obtained as the polystyrene conversion amount using polystyrene as the standard substance in the gel permeation chromatography measurement. The value of the number average molecular weight or weight average molecular weight varies according to the method of taking the baseline of the molecular weight distribution curve of the gel permeation chromatography, while the value of the peak molecular weight is not affected by the method of taking the baseline of the molecular weight distribution curve.

[0070] (Method for producing PAS resin)

[0071] As the manufacturing method of the PAS resin of the present embodiment, as long as a PAS resin having a melt viscosity (V6) of 50 Pa·s or more and 4000 Pa·s or less can be obtained, there is no particular limitation, and examples thereof include: (Manufacturing method 1) a method of adding a dihalogenated aromatic compound in the presence of sulfur and sodium carbonate, and optionally adding a polyhalogenated aromatic compound or other copolymerization component and polymerizing it; (Manufacturing method 2) a method of adding a dihalogenated aromatic compound in the presence of a thioetherifying agent, etc., and optionally adding a polyhalogenated aromatic compound or other copolymerization component and polymerizing it; (Manufacturing method 3) a method of adding other copolymerization components as needed to para-chlorothiophenol and causing it to self-condense; (Manufacturing method 4) a method of melt-polymerizing a diiodide aromatic compound and elemental sulfur while reducing pressure in the presence of a polymerization inhibitor having functional groups such as carboxyl or amino groups, etc. Among these methods, the method of (Manufacturing method 2) is universal and thus preferred. During the reaction, an alkali metal salt or an alkali hydroxide of a carboxylic acid or a sulfonic acid may also be added to adjust the degree of polymerization. Among the methods (production method 2), the method obtained by the following method is particularly preferred: introducing an aqueous thioetherification agent into a mixture containing a heated organic polar solvent and a dihalogenated aromatic compound at a rate that can remove water from the reaction mixture, adding a dihalogenated aromatic compound and a thioetherification agent to the organic polar solvent, and optionally adding a polyhalogenated aromatic compound to react, and controlling the amount of water in the reaction system to be in the range of 0.02 mol to 0.5 mol relative to 1 mol of the organic polar solvent, thereby producing a PAS resin (see Japanese Patent Laid-Open No. 07-228 699 ); or in the presence of a solid alkali metal sulfide and an aprotic polar organic solvent, a dihalogenated aromatic compound and, if necessary, a polyhalogenated aromatic compound or other copolymerization component is added, and the alkali metal hydrosulfide and the organic acid alkali metal salt are controlled within the range of 0.01 mol to 0.9 mol relative to 1 mol of the sulfur source, and the water content in the reaction system is controlled within the range of 0.02 mol or less relative to 1 mol of the aprotic polar organic solvent, and the reaction is carried out simultaneously (see International Publication No. 2010 / 058713).Specific examples of the dihalogenated aromatic compound include p-dihalobenzene, m-dihalobenzene, o-dihalobenzene, 2,5-dihalotoluene, 1,4-dihalonaphthalene, 1-methoxy-2,5-dihalobenzene, 4,4'-dihalobiphenyl, 3,5-dihalobenzoic acid, 2,4-dihalobenzoic acid, 2,5-dihalonitrobenzene, 2,4-dihalonitrobenzene, 2,4-dihaloanisole, p,p'-dihalodiphenyl ether, 4,4'-dihalobiphenyl Ketone, 4,4'-dihalogenodiphenyl sulfone, 4,4'-dihalogenodiphenyl sulfoxide, 4,4'-dihalogenodiphenyl sulfide, and compounds having an alkyl group with a carbon number of 1 to 18 in the aromatic ring of each of the compounds, as polyhalogenated aromatic compounds, there can be listed: 1,2,3-trihalogenobenzene, 1,2,4-trihalogenobenzene, 1,3,5-trihalogenobenzene, 1,2,3,5-tetrahalogenobenzene, 1,2,4,5-tetrahalogenobenzene, 1,4,6-trihalogenonaphthalene, etc. In addition, the halogen atoms contained in each of the compounds are preferably chlorine atoms and bromine atoms.

[0072] The post-treatment method of the reaction mixture containing the PAS resin obtained by the polymerization step is not particularly limited, and examples thereof include: (post-treatment 1) after the polymerization reaction is completed, the reaction mixture is first subjected to distillation to remove the solvent under reduced pressure or normal pressure directly or after adding an acid or a base, and then the solid matter after the solvent is distilled off is washed once or twice or more with a solvent such as water, a reaction solvent (or an organic solvent having an equivalent solubility in the low molecular weight polymer), acetone, methyl ethyl ketone, alcohols, etc., and then neutralized, washed with water, filtered and dried; or (post-treatment 2) after the polymerization reaction is completed, a solvent such as water, acetone, methyl ethyl ketone, alcohols, ethers, halogenated hydrocarbons, aromatic hydrocarbons, aliphatic hydrocarbons (a solvent soluble in the polymerization solvent used and at least a poor solvent for the PAS resin) is added to the reaction mixture as a precipitant to make the PAS resin A method in which a solid product such as an AS resin or an inorganic salt is precipitated, and they are filtered, separated, washed, and dried; or (post-treatment 3) after the polymerization reaction is completed, a reaction solvent (or an organic solvent having an equivalent solubility for the low molecular weight polymer) is added to the reaction mixture and stirred, and then the low molecular weight polymer is removed by filtering, and then the reaction mixture is washed once or twice with a solvent such as water, acetone, methyl ethyl ketone, alcohol, etc., and then neutralized, washed with water, filtered, and dried; (post-treatment 4) after the polymerization reaction is completed, water is added to the reaction mixture, washed with water, filtered, and, if necessary, an acid is added during the water washing to perform an acid treatment and then dried; (5) after the polymerization reaction is completed, the reaction mixture is filtered, washed once or twice with a reaction solvent as needed, and then washed with water, filtered, and dried.

[0073] In the post-treatment methods exemplified in (Post-treatment 1) to (Post-treatment 5), the drying of the PAS resin may be performed in a vacuum, or in the air or in an inert gas atmosphere such as nitrogen.

[0074] (PAS resin composition)

[0075] The gear of the present embodiment may contain PAS resin as a PAS resin composition. By using a PAS resin composition containing PAS resin as a constituent component of the gear of the present embodiment, it is easy to impart desired material properties.

[0076] The melt viscosity (V6) of the PAS resin composition of the present embodiment is preferably in the range of 50 Pa·s or more and 4000 Pa·s or less. The upper limit of the melt viscosity (V6) of the PAS resin composition of the present embodiment is preferably 2000 Pa·s or less, more preferably 700 Pa·s or less, and further preferably 300 Pa·s or less. In addition, the lower limit of the melt viscosity (V6) of the PAS resin of the present embodiment is preferably 70 Pa·s or more, more preferably 80 Pa·s or more, and further preferably 90 Pa·s or more. The upper and lower limits can be arbitrarily combined.

[0077] By using a PAS resin composition with a viscosity of 50 Pa·s or more, the strength of the gear increases, thereby improving the durability of the entire gear or reducing burrs during molding. On the other hand, by using a PAS resin composition with a melt viscosity (V6) of 4000 Pa·s or less, the PAS resin composition can be filled to the tooth top during injection molding, thereby improving the mold transferability of the gear and making it possible to produce a gear with a good appearance.

[0078] The PAS resin composition of the present embodiment preferably contains 50 to 100% by mass of the PAS resin relative to the total amount (100% by mass) of the PAS resin, more preferably 60 to 95% by mass of the PAS resin, and even more preferably 70 to 95% by mass of the PAS resin.

[0079] The PAS resin composition of the present embodiment may contain fillers as an arbitrary component as needed. As the filler, as long as the effect of the present disclosure is not damaged, known conventional materials may also be used, for example, fillers of various shapes such as fibrous, granular or plate-like non-fibrous, etc. may be cited. Specifically, fibrous fillers such as fibers such as glass fiber, carbon fiber, silane glass fiber, ceramic fiber, aramid fiber, metal fiber, potassium titanate, silicon carbide, calcium silicate, wollastonite, and natural fibers may be used, and non-fibrous fillers such as glass beads, glass flakes, barium sulfate, clay, pyrophyllite, bentonite, sericite, mica, mica, talc, attapulgite, ferrite, calcium silicate, calcium carbonate, glass beads, zeolite, milled fibers, and calcium sulfate may also be used in addition.

[0080] In the present embodiment, the filler is not an essential component, and when mixed, its content is not particularly limited as long as the effect of the present disclosure is not impaired. The amount of the filler mixed, for example, is preferably 1 part by mass or more, more preferably 10 parts by mass or more, to preferably 600 parts by mass or less, more preferably 200 parts by mass or less, relative to 100 parts by mass of the PAS resin. Within the above range, the PAS resin composition exhibits good mechanical strength and moldability, and is therefore preferred.

[0081] The PAS resin composition or constituent of the present embodiment is preferably substantially free of cellulose nanofibers. Moreover, the so-called "substantially free of cellulose nanofibers" refers to the case where cellulose nanofibers are included in the PAS resin composition or constituents, and relative to the total amount of PAS resin and cellulose nanofibers, the content of cellulose nanofibers is preferably less than 0.5% by mass, more preferably less than 0.3% by mass. If the content of cellulose nanofibers is more than 0.5% by mass, the cellulose nanofibers decompose and carbonize or produce decomposition gas when making the PAS resin composition, and the mechanical strength decreases.

[0082] The PAS resin composition of the present embodiment preferably contains a silane coupling agent. In the present embodiment, by further containing a silane coupling agent as a constituent component constituting the gear, good moldability, particularly mold release properties, are achieved, and mechanical strength is further improved.

[0083] The silane coupling agent that can be contained in the PAS resin composition of the present embodiment is not particularly limited as long as the effects of the present disclosure are not impaired. Preferred silane coupling agents include silane coupling agents having a functional group that reacts with a carboxyl group, such as an epoxy group, an isocyanate group, an amino group, or a hydroxyl group. Examples of such silane coupling agents include epoxy group-containing alkoxysilane compounds such as γ-glycidyloxypropyltrimethoxysilane, γ-glycidyloxypropyltriethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-isocyanatepropyltrimethoxysilane, γ-isocyanatepropyltriethoxysilane, γ-isocyanatepropylmethyldimethoxysilane, γ-isocyanatepropylmethyldiethoxysilane, and γ-isocyanatepropylethyldimethoxysilane. Alkoxysilane compounds containing an isocyanate group such as methoxysilane, γ-isocyanatopropylethyldiethoxysilane, and γ-isocyanatopropyltrichlorosilane, alkoxysilane compounds containing an amino group such as γ-(2-aminoethyl)aminopropylmethyldimethoxysilane, γ-(2-aminoethyl)aminopropyltrimethoxysilane, and γ-aminopropyltrimethoxysilane, and alkoxysilane compounds containing a hydroxyl group such as γ-hydroxypropyltrimethoxysilane and γ-hydroxypropyltriethoxysilane. In the present disclosure, the silane coupling agent is not an essential component. When blended, the amount thereof is not particularly limited as long as the effects of the present disclosure are not impaired, and is preferably in the range of 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, and preferably 10 parts by mass or less, more preferably 5 parts by mass or less, relative to 100 parts by mass of the PAS resin. In the above range, the PAS resin composition has good moldability, particularly mold releasability, and the molded product has excellent adhesion with the epoxy resin, and further has improved mechanical strength, which is preferred.

[0084] The PAS resin composition of the present embodiment may contain a thermoplastic elastomer as an arbitrary component as needed. As a thermoplastic elastomer, a polyolefin elastomer, a fluorine-based elastomer or a silicone-based elastomer can be cited, wherein as a preferred thermoplastic elastomer, a polyolefin elastomer can be cited. In the case of adding these elastomers, as long as the effect of the present disclosure is not damaged, the amount thereof is not particularly limited, and relative to 100 parts by mass of PAS resin, preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more to preferably 10 parts by mass or less, more preferably 5 parts by mass or less. Within the range, the impact resistance of the obtained PAS resin composition is improved, so it is preferred.

[0085] For example, the polyolefin-based elastomer may include a homopolymer of an α-olefin, a copolymer of two or more α-olefins, or a copolymer of one or more α-olefins and a vinyl polymerizable compound having a functional group. In this case, the α-olefin may include ethylene, propylene, 1-butene, and other α-olefins having a carbon number ranging from 2 to 8. In addition, the functional group may include a carboxyl group, an acid anhydride group (-C(=O)OC(=O)-), an epoxy group, an amino group, a hydroxyl group, a mercapto group, an isocyanate group, an oxazoline group, and the like. Furthermore, examples of the vinyl polymerizable compound having the functional group include: vinyl acetate; α,β-unsaturated carboxylic acids such as (meth) acrylic acid; alkyl esters of α,β-unsaturated carboxylic acids such as methyl acrylate, ethyl acrylate, and butyl acrylate; metal salts of α,β-unsaturated carboxylic acids such as ionomers (metals are alkali metals such as sodium, alkaline earth metals such as calcium, and zinc); glycidyl esters of α,β-unsaturated carboxylic acids such as glycidyl methacrylate; α,β-unsaturated dicarboxylic acids such as maleic acid, fumaric acid, and itaconic acid; and one or more derivatives of the α,β-unsaturated dicarboxylic acids (monoesters, diesters, and anhydrides). The thermoplastic elastomer may be used alone or in combination of two or more.

[0086] Furthermore, the PAS resin composition of the present embodiment may be appropriately blended with synthetic resins such as polyester resins, polyamide resins, polyimide resins, polyetherimide resins, polycarbonate resins, polyphenylene ether resins, polysulfone resins, polyethersulfone resins, polyetheretherketone resins, polyetherketone resins, polyarylene resins, polyethylene resins, polypropylene resins, polytetrafluoroethylene resins, polyvinylidene fluoride resins, polystyrene resins, ABS resins, phenol resins, urethane resins, and liquid crystal polymers (hereinafter referred to as synthetic resins) as arbitrary components in addition to the above components. In the present disclosure, the synthetic resins are not essential components, and when blended, the blending ratio is not particularly limited as long as the effects of the present disclosure are not impaired. In addition, the blending ratio varies depending on each purpose and cannot be generally specified, but the ratio of the synthetic resin blended in the PAS resin composition of the present embodiment may be, for example, 5 parts by mass or more and 15 parts by mass or less relative to 100 parts by mass of the PAS resin. In other words, the ratio of the PAS resin to the total of the PAS resin and the synthetic resin is preferably in the range of (100 / 115) or more, and more preferably in the range of (100 / 105) or more, based on mass.

[0087] In addition, the PAS resin composition of the present embodiment may also contain, as required, known and commonly used additives such as colorants, antistatic agents, antioxidants, heat stabilizers, ultraviolet stabilizers, ultraviolet absorbers, foaming agents, flame retardants, flame retardant aids, rust inhibitors, and coupling agents as arbitrary components. These additives are not essential components, and, for example, are preferably in the range of 0.01 parts by mass or more, and preferably in the range of 100 parts by mass or less, with respect to 1000 parts by mass of the PAS resin, and can be appropriately adjusted and used according to the purpose or use so as not to impair the effects of the present disclosure.

[0088] <Preferred form of PAS resin composition>

[0089] A preferred form of the PAS resin composition as a constituent component of the gear of the present embodiment contains a PAS resin having a melt viscosity (V6) of 50 Pa·s to 4000 Pa·s, a silane coupling agent and a filler, and the total content of the PAS resin, the silane coupling agent and the filler is preferably 50% to 100% by mass, and more preferably 70% to 100% by mass, relative to the total amount (100% by mass) of the PAS resin composition.

[0090] By using the PAS resin composition of the above composition as a constituent component of the gear of this embodiment, it is easy to control the dimensional change rate of the gear and / or the water absorption rate of the gear within a specified range (for example, the dimensional change rate caused by temperature change is less than 0.7%, and / or the water absorption rate is greater than 0.5%).

[0091] Thus, the gear, worm gear, and robot of the present embodiment have a lower dimensional change rate due to heat and water absorption, and can have better durability and dimensional accuracy under high temperature and high humidity. In addition, the PAS resin has a carboxyl group in its molecule, and the content of the carboxyl group present in the molecular structure of the PAS resin is preferably 10 μmol or more and 200 μmol or less relative to 1 g of the PAS resin.

[0092] The carboxyl group is reactive with a coupling agent, and thus can exhibit an effect of improving the durability of the gear by using it in combination with a coupling agent.

[0093] The PAS resin composition of the present embodiment is prepared by mixing a main component and other optional components as needed. The method for producing the PAS resin composition used in the present disclosure is not particularly limited, and examples thereof include a method of mixing a main component and an optional component as needed and performing melt kneading, and more specifically, a method of uniformly performing dry mixing using a tumbler or Henschel mixer as needed, and then feeding the mixture into a twin-screw extruder and performing melt kneading.

[0094] Melt kneading can be carried out by heating the resin temperature to a temperature range above the melting point of the PAS resin, preferably a temperature range above the melting point + 10°C, more preferably above the melting point + 10°C, further preferably above the melting point + 20°C, and preferably below the melting point + 100°C, more preferably below the melting point + 50°C.

[0095] As the melt kneader, from the viewpoint of dispersibility or productivity, a twin-screw kneading extruder is preferred. For example, it is preferred to perform melt kneading while appropriately adjusting the discharge amount of the resin component in the range of 5 to 500 (kg / hr) and the screw speed in the range of 50 to 500 (rpm). It is further preferred to perform melt kneading under the condition that their ratio (discharge amount / screw speed) is in the range of 0.02 to 5 (kg / hr / rpm). In addition, the addition and mixing of each component to the melt kneader can be carried out simultaneously or separately. For example, when adding additives to the components, from the viewpoint of dispersibility, it is preferred to feed the additives from the side feeder of the twin-screw kneading extruder into the extruder. Regarding the position of the side feeder, the ratio of the distance from the extruder resin input part (top feeder) to the side feeder to the total length of the screw of the twin-screw kneading extruder is preferably 0.1 or more, more preferably 0.3 or more. In addition, the ratio is preferably 0.9 or less, more preferably 0.7 or less.

[0096] The PAS resin composition of the present disclosure obtained by melt kneading in this manner is a molten mixture containing the main component, and optionally added optional components and components derived therefrom. After the melt kneading, the molten PAS resin composition is preferably processed into a form such as pellets, chips, granules, powder, etc. by a known method, such as extruding the molten PAS resin composition into a strand shape, and then pre-dried at a temperature range of 100° C. to 150° C. as needed.

[0097] (Preferred gear shape)

[0098] Regarding a worm wheel, a worm, and a worm-type gear which are preferred forms of the gear according to the present embodiment, one embodiment of the gear of the present disclosure will be mainly described with reference to the drawings.

[0099] <Worm gear>

[0100] Figure 1 Schematic diagram showing the structure of a worm wheel 1 according to an embodiment of the present disclosure. Figure 1 , the structure of the worm wheel 1 according to one embodiment will be mainly described.

[0101] The worm wheel 1 of this embodiment is a so-called spur gear (flat gear). More specifically, the worm wheel 1 has a first tooth portion 2 protruding radially outward, and a (roughly) disc-shaped main body portion having the first tooth portion 2 formed on the outer periphery. Furthermore, the grooves 3 formed between the first tooth portion 2 and the adjacent first tooth portion 2 are periodically arranged.

[0102] In other words, the worm wheel 1 has a shape in which the first tooth portion 2 is arranged at a predetermined interval on a (roughly) disc-shaped side surface. In addition, a through hole 4 is formed in the center of the main body portion for inserting an axial body such as a camshaft. If necessary, a recessed portion for arranging a flange of the camshaft may be formed on the outer periphery of the through hole 4 on one side of the main body portion. In addition, if necessary, a recessed portion for arranging a mounting member (for example, a stop screw mechanism) for mounting other gears on the camshaft may be formed on the outer periphery of the through hole 4 on the other side of the main body portion.

[0103] The worm wheel 1 has a rotating shaft, and the rotating shaft is rotatably supported by a worm wheel base via a bearing, and can serve as an output side of a driving force of a worm gear 100 described later.

[0104] A preferred gear of the present embodiment is a worm wheel 1 having a first tooth portion 2 formed on the outer periphery and containing a PAS resin having a melt viscosity (V6) of 50 Pa·s to 4000 Pa·s as a constituent component.

[0105] The worm wheel 1 contains PAS resin or a PAS resin composition, and thus has a low dimensional change rate caused by heat and water absorption, and excellent durability and dimensional accuracy under high temperature and high humidity. Therefore, it is believed that the effect is achieved by reducing the rattle or noise caused by the meshing of the second tooth portion 5 and the first tooth portion 2 of the worm 10, or the combination with other components.

[0106] In addition, Figure 1 In the embodiment, the worm wheel 1 is constituted of only PAS resin or PAS resin composition, but a part of the worm wheel 1 may be constituted of PAS resin or PAS resin composition. For example, only the first tooth portion 2 may be constituted of PAS resin or PAS resin composition, or a part of the through hole 4 through which a shaft body such as a camshaft is inserted may be constituted of a metal material. The metal material is not particularly limited, and examples thereof include metals containing one or more selected from iron, steel materials, stainless steel, aluminum, magnesium-aluminum alloy, magnesium, magnesium alloy, copper, copper alloy, titanium and titanium alloy.

[0107] <Worm>

[0108] Figure 2 Schematic diagram showing the structure of the worm 10 according to one embodiment of the present disclosure. Figure 2 The structure of the worm 10 according to one embodiment will be mainly described.

[0109] The worm 10 of the present embodiment is a (roughly) cylindrical gear having a tooth surface with a shape in which the groove 6 is continuously cut in a spiral shape. In more detail, the worm 10 has a second tooth portion 5 protruding radially outward in a spiral shape, and a (roughly) cylindrical worm shaft 8 having the second tooth portion 5 formed on the outer periphery. Moreover, the groove 6 formed between the second tooth portion 5 and the adjacent second tooth portion 5 is periodically arranged. In addition, the worm 10 has a worm shaft 8, a spiral second tooth portion 5, and a fixing hole 7 for inserting or fixing a shaft or a through shaft (not shown). The worm 10 is rotatably mounted on a worm base including a bearing. Therefore, as needed, a bearing portion (not shown) may also be provided on one end side and / or the other end side of the worm shaft 8, and the bearing portion is fixed to a bearing of a worm base that can rotatably support the worm 10.

[0110] One end of the worm 10 is connected to the rotating shaft of a motor (not shown) as a power source, and can be the input side of the driving force of the worm gear 100 described later. Therefore, the fixing hole 7 can be a portion connected to the rotating shaft of the motor (not shown) as a power source.

[0111] The second tooth portion 5 is formed coaxially with the worm shaft 8, for example, in a shape that is continuously cut into the side surface of a cylindrical shape having a larger diameter than the worm shaft 8 in a spiral shape. Figure 2 The spirals rotating in opposite directions cut into the shape continuously.

[0112] A preferred gear of the present embodiment is a worm 10 having a second tooth portion 5 formed on the outer circumference and containing a PAS resin having a melt viscosity (V6) of 50 Pa·s to 4000 Pa·s as a constituent component.

[0113] The worm 10 contains PAS resin or a PAS resin composition, and thus has a low dimensional change rate caused by heat and water absorption, and excellent durability and dimensional accuracy under high temperature and high humidity. Therefore, it is believed that the effect is achieved by reducing the shaking or noise caused by the meshing of the first tooth portion 2 and the second tooth portion 5 of the worm wheel 1 and the combination with other components such as the insertion shaft of the motor.

[0114] In addition, Figure 2 In the embodiment, the worm 10 is made of only PAS resin or PAS resin composition, but part of the worm 10 may be made of PAS resin or PAS resin composition. For example, only the second tooth portion 5 may be made of PAS resin or PAS resin composition, or part of the worm shaft 8 or the fixing hole 7 may be made of metal material. The metal material is not particularly limited, and examples thereof include one or more metals selected from iron, steel materials, stainless steel, aluminum, magnesium-aluminum alloy, magnesium, magnesium alloy, copper, copper alloy, titanium and titanium alloy.

[0115] <Worm gear>

[0116] Figure 3 Schematic diagram showing the structure of a worm gear 100 according to an embodiment of the present disclosure. Figure 3 The structure of the worm gear 100 according to one embodiment will be mainly described.

[0117] The worm gear 100 of the present embodiment is a gear having a worm wheel 1 and a worm 10. The worm gear 100 is a rotational motion transmission mechanism composed of the worm 10 and the worm wheel 1, wherein the worm 10 has a tooth surface including a helical second tooth portion 5, and the worm wheel 1 has a tooth surface including a first tooth portion 2 meshing with the helical second tooth portion 5.

[0118] The worm wheel 1 is rotatably supported around a rotation axis different in direction from that of the worm 10, and has a tooth surface including a first tooth portion 2 on the outer periphery. In addition, the worm 10 is rotatably supported around a rotation axis different in direction from that of the worm wheel 1, and has a tooth surface including a second tooth portion 5 formed in a spiral shape on the outer periphery. The tooth portion 2 (first tooth portion 2) of the worm wheel 1 meshes with the tooth portion 5 (second tooth portion 5) of the worm 10.

[0119] When the worm 10 rotates in the direction of arrow θ1 and the second tooth portion 5 of the worm 10 moves in the direction of arrow X1, the worm wheel 1 is driven to rotate in the direction indicated by arrow φ1. Conversely, when the worm wheel 1 is driven to rotate in the direction of arrow φ1, the tooth portion 5 of the worm 10 moves in the direction of arrow X1 and the worm 10 is driven to rotate in the direction of arrow θ1.

[0120] On the other hand, when the worm 10 rotates in the direction of arrow θ2 and the tooth portion 5 of the worm 10 moves in the direction of arrow X2, the worm wheel 1 is driven to rotate in the direction indicated by arrow φ2. In addition, conversely, when the worm wheel 1 rotates in the direction indicated by arrow φ2, the tooth portion 5 of the worm 10 moves in the direction of arrow X2 and the worm 10 is driven to rotate in the direction of arrow θ2.

[0121] The preferred gear of this embodiment is a worm gear 100, which comprises: a worm wheel 1 having a first tooth portion 2 formed on the periphery and comprising a PAS resin having a melt viscosity (V6) of 50 Pa·s to 4000 Pa·s as a constituent component; and a worm 10 having a second tooth portion 5 formed on the periphery and meshing with the first tooth portion 2 and comprising a PAS resin having a melt viscosity (V6) of 50 Pa·s to 4000 Pa·s as a constituent component.

[0122] The worm wheel 1 and the worm 10 constituting the worm gear 100 contain PAS resin or a PAS resin composition, and thus have a low dimensional change rate caused by heat and water absorption, and excellent durability and dimensional accuracy under high temperature and high humidity.

[0123] This is considered to be effective in that the worm wheel 1 and the worm 10 are optimally meshed with each other, and that the rattle and noise caused by the combination with other components such as the insertion shaft of the motor are reduced.

[0124] <Physical properties of gears>

[0125] In the gear of the present embodiment, the dimensional change rate due to water absorption is preferably 0.2% or less, more preferably 0.15% or less, and further preferably 0.1% or less.

[0126] Generally speaking, the phenomenon of water absorption of resin is that water penetrates into the amorphous part of the resin, and the polymer chain expands. Therefore, the amount of water retained between the polymer chains is proportional to the dimensional change. Therefore, if the dimensional change rate caused by water absorption is less than 0.2%, even if the gear of this embodiment is used for a worm wheel, a worm, etc., it is not easy to affect the meshing of the teeth or the combination with other components such as the insertion shaft of the motor, and shows better dimensional accuracy under high humidity. That is, the gear of this embodiment uses PAS resin with low water absorption as a constituent component, so the dimensional change rate caused by water absorption is low, and it can have excellent dimensional accuracy under high humidity.

[0127] The method for measuring the dimensional change rate caused by the water absorption is described in the Example column described later, and the change rate (%) of the tooth top circle diameter of the gear before and after the gear of this embodiment is immersed in water is = {(h1-h0) / h0}×100 as the dimensional change rate caused by water absorption.

[0128] The "tooth tip circle diameter" in this specification refers to the numerical average of the values ​​obtained by measuring the tooth tip circle diameter of the gear at any 10 locations. In addition, the tooth tip circle diameter is measured by measuring the diameter of the circle connecting the front ends of the teeth. For example, Figure 1 As shown in FIG. 1 , the tooth tip circle diameter Ra refers to the length of a line connecting the front end of the tooth portion 2 of the gear (e.g., worm wheel 1), the center of the gear (e.g., worm wheel 1), and the front end of the tooth portion 2 opposite to the front end of the tooth portion 2 of the gear (e.g., worm wheel 1). In addition, the dimensional change rate (%) in this specification refers to a rate with the length at a reference time (e.g., before water absorption or temperature change) during water absorption or temperature change as the denominator and the length from the reference time to the comparison time accompanied by water absorption or temperature change as the numerator, and is an absolute value. Therefore, strictly speaking, the dimensional change rate (%) caused by a temperature change from 0°C to 80°C is the absolute value of the following formula (I).

[0129] In the gear of this embodiment, the dimensional change rate (%) caused by the temperature change from 0°C to 80°C is expressed by the following formula (I), and the dimensional change rate (%) is preferably 0.7% or less, more preferably 0.65% or less, and further preferably 0.6% or less.

[0130] [Number 3]

[0131]

[0132] (In the formula (I), L 80 Indicates the addendum diameter of the gear at 80°C, L 0 Indicates the addendum diameter of the gear at 0°C).

[0133] If the dimensional change rate due to temperature change is 0.7% or less, even if the gear of the present embodiment is used for a worm wheel, a worm, etc., it is not easy to affect the meshing of the teeth or the combination with other components such as the insertion shaft of the motor, and it shows better durability and dimensional accuracy at high temperatures. That is, the gear of the present embodiment uses PAS resin or PAS resin composition with a low linear thermal expansion coefficient as a constituent component, so the dimensional change rate due to heat is low, and it can have excellent durability and dimensional accuracy at high temperatures.

[0134] In the gear of the present embodiment, the modulus is preferably within a range of 0.5 mm to 25 mm.

[0135] In the gear of the present embodiment, the tooth thickness is preferably within a range of 0.8 mm to 40 mm.

[0136] In the gear of the present embodiment, the pitch circle diameter is preferably within a range of 1.5 mm to 3200 mm.

[0137] The modulus and the tooth thickness are related to each other by the relationship of 1.6×modulus=tooth thickness (mm). The modulus is represented by [base circle diameter (unit: mm)]÷(number of teeth).

[0138] <Gear Manufacturing Method>

[0139] The gear of the present embodiment is preferably formed by molding a PAS resin or a PAS resin composition. In addition, the method for manufacturing the gear of the present embodiment includes a step of melt-molding the PAS resin composition. This will be described in detail below.

[0140] The PAS resin or PAS resin composition as a constituent component of the gear of the present embodiment can be used for various moldings such as injection molding, gas injection molding, compression molding, extrusion molding of composites, sheets, tubes, etc., drawing molding, blow molding, transfer molding, etc., and is particularly suitable for injection molding applications because of its excellent demolding properties. In the case of molding by injection molding, various molding conditions are not particularly limited, and molding can usually be performed by general methods. For example, in an injection molding machine, after the PAS resin composition is melted in a temperature range where the resin temperature is above the melting point of the PAS resin, preferably in a temperature range of above the melting point + 10°C, more preferably in a temperature range of melting point + 10°C to melting point + 100°C, and further preferably in a temperature range of melting point + 20 to melting point + 50°C, it can be injected into the mold from the resin discharge port for molding. At this time, the mold temperature can also be set to a known temperature range, such as room temperature (23°C) to 300°C, preferably 120°C to 180°C.

[0141] The worm gear 100 described above can be used in any machine. For example, the worm gear 100 can be applied to industrial robot arms, actuators for medical use, water swirl parts, and automobile parts. Hereinafter, as an example, an embodiment of using the worm gear 100 in a robot, more specifically, a robot arm, will be described.

[0142] Figure 4 Is has Figure 3 Schematic diagram of a robot arm mechanism 1000 having a worm gear 100.

[0143] The robot arm mechanism 1000 includes, in addition to the worm gear 100, a first arm A1 connected to a robot body, etc., and a second arm A2 including a portion that operates at the front end of the robot arm mechanism 1000. The robot arm mechanism 1000 includes the worm gear 100 at a joint J between the first arm A1 and the second arm A2.

[0144] In the robot arm mechanism 1000 , the worm gear 100 operates so that the second arm A2 having a length L performs circular motion with the joint J as a fulcrum. The robot arm mechanism 1000 drives the worm gear 100 based on a control signal to move the tip of the second arm A2 to a specified position.

[0145] exist Figure 4 In the embodiment of the present invention, the worm gear 100 is used for the arm mechanism of the robot, but the use of the worm gear 100 is not limited thereto. The worm gear 100 may be used in any other component in addition to or instead of the arm mechanism of the robot. The robot may also have the worm gear 100 in any component that needs to be driven by a gear.

[0146] Example

[0147] Hereinafter, the present invention will be described using Examples and Comparative Examples, but the present invention is not limited to these Examples. It should be noted that, in the following, "%" or "part" is based on mass unless otherwise specified.

[0148] <Raw materials used in Examples and Comparative Examples>

[0149] <PAS resin>

[0150] Polyphenylene sulfide resin (hereinafter referred to as PPS resin), melt viscosity 30 Pa·s, carboxyl group 30 μmol / g PPS resin, melt viscosity 50 Pa·s, carboxyl group 30 μmol / g

[0151] PPS resin, melt viscosity 300 Pa·s, carboxyl group 30 μmol / g

[0152] PPS resin, melt viscosity 4000 Pa·s, carboxyl group 30 μmol / g

[0153] PPS resin, melt viscosity 7000 Pa·s, carboxyl group 30 μmol / g

[0154] <Silane coupling agent>

[0155] Epoxy silane: 3-glycidyloxypropyltrimethoxysilane, "SH-6040" manufactured by Dow Corning Corporation

[0156] Aminosilane: N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, Shin-Etsu Chemical Co., Ltd. "KBM-603"

[0157] <Other resins>

[0158] POM (polyacetal resin) "M90-44" manufactured by Polyplastics Co., Ltd.

[0159] PA6 (polyamide resin) Toray Industries, Inc. "CM1017"

[0160] <Evaluation Methods in Examples and Comparative Examples>

[0161] (1) Quantification of carboxyl groups

[0162] The quantitative determination of the carboxyl groups in the PPS resins obtained in Examples and Comparative Examples was carried out according to the following procedure.

[0163] As a pretreatment, the PPS resin used in each example and comparative example was temporarily dissolved in dimethyl imidazolidinone (DMI) under an inert atmosphere at 210°C, and then cooled to precipitate the PPS resin again. Then, the obtained slurry was fully washed and filtered with ion exchange water several times, and then temporarily adjusted to a pH of less than 2.5 with hydrochloric acid, and then repeatedly washed with ion exchange water several times. The obtained filter cake was then dried in a hot air dryer at 120°C. The dried solid matter was used as a sample.

[0164] Next, each sample obtained was pressed into a disk shape using a pressing machine and measured using a microscopic FT-IR device. Then, the absorption at 1705 cm -1 The absorption relative to 2666cm -1 Then, a predetermined amount of p-chlorophenylacetic acid was mixed with the PPS resin used in each example and comparative example, and the absorption curve at 1705 cm was obtained by the same operation. -1 The absorption intensity relative to 2666cm -1 A calibration curve is obtained by plotting the relative intensity of the absorption intensity of the PPS resin, and the numerical value obtained from the calibration curve is set as the amount of carboxyl groups contained in the PPS resin.

[0165] (2) Determination of dimensional change rate (%)

[0166] (2-1) Determination of the dimensional change rate of gears caused by water absorption

[0167] After drying the gears of the worm wheels and worm gears produced in the examples and comparative examples at 50°C for 24 hours, the gears were returned to room temperature (23°C) in a dryer, and the tooth tip circle diameters of the gears after drying were measured at any 10 tooth positions, and the numerical average thereof was set as the tooth tip circle diameter (h0) of the gears after drying. Thereafter, the gears were immersed in distilled water at room temperature (20°C to 28°C) for 80 days, and the tooth tip circle diameters of the gears after immersion were measured at any 10 tooth positions, and the numerical average thereof was set as the tooth tip circle diameter (h1) of the gears after immersion. Then, the change rate (%) of the tooth tip circle diameter before and after immersion = {(h1-h0) / h0}×100 was set as the dimensional change rate caused by water absorption.

[0168] (2-2) Determination of the dimensional change rate of gears caused by temperature changes

[0169] The dimensional change rate (%) of each worm wheel and each worm gear produced in the examples and comparative examples due to a temperature change from 0° C. to 80° C. is defined by the following formula (I).

[0170] [Number 4]

[0171]

[0172] (In the formula (I), L 80 Indicates the addendum diameter of the gear at 80°C, L 0 Indicates the tip circle diameter of the gear at 0°C)

[0173] After the gear is dried at 50°C for 24 hours, the addendum diameter of the gear maintained in a constant temperature bath set at 0°C for 1 hour is measured at 10 random tooth positions within 30 seconds, and the average value is set as the addendum diameter of the gear (L 0 After that, the gear was kept in a thermostatic bath set at 80°C for 1 hour, and the tooth top circle diameter of the gear just taken out of the thermostatic bath was measured at any 10 tooth positions within 30 seconds, and the average value of the number was set as the tooth top circle diameter of the gear (L 80 ).

[0174] (3) Evaluation of formability

[0175] The obtained pellets were supplied to a Sumitomo Heavy Industries injection molding machine (SE-75D-HP) with the barrel temperature set at 320°C, and injection molding was performed using a mold adjusted to 150°C to obtain a gear. The appearance of the obtained gear was visually observed, and the case where the surface was glossy and the resin was filled to the tooth top was rated as good, and the case where the surface was matte and the resin was not filled to the tooth top was rated as bad. In addition, the case where a large amount of gas was generated during injection molding and molding was difficult was rated as unmoldable, and the case where burrs were generated on the tooth top of the gear was rated as large burrs.

[0176] (4)M w / M top Compare

[0177] The weight average molecular weight (M) of the PPS resin was determined using gel permeation chromatography under the following measurement conditions: w ) and peak molecular weight (M top ) is measured. According to the obtained M w and M top Calculate M w / M top Six monodisperse polystyrenes were used for calibration.

[0178] Equipment: Ultra-high temperature polymer molecular weight distribution measuring device (SSC-7000 manufactured by Senshu Scientific Co., Ltd.)

[0179] Column: UT-805L (manufactured by Showa Denko K.K.)

[0180] Column temperature: 210°C

[0181] Solvent: 1-Chloronaphthalene

[0182] Measurement method: Ultraviolet (UV) detector (360nm)

[0183] (5) Determination of melt viscosity (V6)

[0184] For PPS resin, a flow tester, CFT-500C, manufactured by Shimadzu Corporation, was used at 300°C and a load of 1.96×10 6 After maintaining the temperature at Pa and L / D = 10 / 1 for 6 minutes, the melt viscosity was measured.

[0185] <Examples 1 to 10 and Comparative Examples 1 to 10>

[0186] The materials were mixed based on the composition and the amount of each compounding described in Table 1. Then, these compounding materials were put into a twin-screw extruder "TEX-30 (product name)" with a vent manufactured by Nippon Steel Works, Ltd., and melt-kneaded at a resin component discharge rate of 25 kg / hr, a screw speed of 200 rpm, and a set resin temperature of 330° C. to obtain pellets of a PPS resin composition.

[0187] The worm and worm wheel components in Examples 1 to 10 and Comparative Examples 1 to 10 were obtained by injection molding at a barrel temperature of 320°C and a mold temperature of 150°C using the pelletized PPS resin compositions obtained above. The shape of each worm was a modulus of 0.8 mm, 1 tooth, right twist, and a lead angle of 3.17°. In addition, the shape of any worm wheel was a helical gear with a modulus of 0.8, a pressure angle of 20°, a number of teeth of 38, and a lead angle of 3.17°.

[0188] Various evaluations were performed on the worms and worm wheels of Examples 1 to 10 and Comparative Examples 1 to 10. Table 1 shows the results.

[0189] [Table 1]

[0190]

[0191] [Table 2]

[0192]

[0193] The worm and worm wheel obtained in the examples had a lower dimensional change rate due to heat and water absorption than the worm and worm wheel obtained in the comparative examples, and thus were confirmed to have excellent durability and dimensional accuracy under high temperature and high humidity.

[0194] In addition, the worms and worm wheels obtained in Comparative Examples 1 to 6 could not be evaluated for the dimensional change rate due to water absorption and the dimensional change rate due to temperature change due to molding defects and the like.

[0195] In addition, this application claims the benefit and priority of Japanese Patent Application No. 2022-107384 filed on July 1, 2022, the entire contents of which are incorporated herein by reference.

[0196] [Explanation of symbols]

[0197] 1 Worm gear

[0198] 2 First tooth

[0199] 3 slots

[0200] 4 Through holes

[0201] 5 Second tooth

[0202] 6 slots

[0203] 7 Fixing holes

[0204] 8 Worm shaft

[0205] 10 Worm

[0206] 100 Worm gear

[0207] Ra Tip circle diameter

[0208] A1 First Arm

[0209] A2 Second Arm

[0210] J Joint

[0211] L Length

[0212] Δθ Angle error

Claims

1. A gear having a first tooth portion formed on an outer periphery and comprising a polyarylene sulfide resin having a melt viscosity V6 of 50 Pa·s to 4000 Pa·s as a constituent component.

2. The gear according to claim 1, in, The dimensional change rate caused by the temperature change from 0°C to 80°C represented by the following formula (I) is 0.7% or less, wherein the unit of dimensional change rate is %, [Number 1] In the formula (I), L 80 Indicates the addendum diameter of the gear at 80°C, L 0 Indicates the tip circle diameter of the gear at 0°C. 3 . The gear according to claim 1 , further comprising cellulose nanofibers as the constituent component, wherein the content of the cellulose nanofibers is less than 0.5% by mass based on the total amount of the polyarylene sulfide resin and the cellulose nanofibers. 4 . The gear according to claim 1 , further comprising a silane coupling agent as the constituent component.

5. A worm gear, comprising: the gear according to claim 1 or 2 as a worm wheel, and a worm having a second tooth portion meshing with a first tooth portion of the gear, The worm includes a polyarylene sulfide resin having a melt viscosity V6 of 50 Pa·s to 4000 Pa·s as a constituent component. 6 . A gear system for a robot, comprising the worm gear according to claim 5 .

7. A robot comprising the robot gear system according to claim 6.